The world's maritime industry in the 21st century: Challenges, expectations, and directions - Ali, Ismail (Science, Technology, and Education Care, 2025)
The maritime industry is a cornerstone of global trade, responsible for transporting over 90% of the world’s goods. However, the 21st century has brought both new opportunities and unprecedented challenges for the sector. With the continued growth of global trade, rapid technological advancements, and shifting geopolitical dynamics, the maritime industry faces increasing pressure to adapt and innovate. Key challenges include the need for sustainability in the face of environmental concerns, such as the reduction of greenhouse gas emissions, marine pollution, and biodiversity loss. Technological advancements, such as automation, digitalization, and the adoption of green technologies, offer promising solutions but also pose operational and regulatory hurdles. Geopolitical tensions, particularly in strategically important regions like the South China Sea, add further complexity to the security and stability of global shipping routes. Furthermore, the evolving expectations of governments, businesses, and the public demand the maritime industry prioritize environmental responsibility, workforce welfare, and safety. This paper explores these challenges, outlines the expectations for the maritime sector, and identifies the key directions that will shape the future of the industry, emphasizing the role of innovation, collaboration, and sustainable practices. A comprehensive understanding of these dynamics is crucial for stakeholders to navigate the complexities of the modern maritime environment and ensure the industry's resilience and growth in the coming decades